Late Transition Metal Complexes of Group 13 Lewis Acid-Containing Ambiphilic Ligands - Cowie, Bradley E. (My University, 2015)
The coordination chemistry of a structurally rigid phosphine–thioether–borane ligand, TXPB (TXPB = 2,7-di-tert-butyl-5-diphenylboryl-4-diphenylphosphino-9,9-dimethylthioxanthene), as well as the Group 13 Lewis acid-appended analogues of 1,1'-bis(phosphino)ferrocene, FcPPB (FcPPB = [Fe(η5-C5H4PPh2){η5-C5H4PtBu(C6H4BPh2-o)}]) and FcPPAl (FcPPAl = [Fe(η5-C5H4PPh2){η5-C5H4PtBu(C6H4AlMe2-o)}]) has been explored with a range of transition metal pre-cursors. Previously reported [Rh(μ-Cl)(CO)(TXPB)] (1) reacted with Me3SiBr, Me3SiI, [NMe4]F, Tl[PF6] and NaBH4 to provide [Rh(μ-Br)(CO)(TXPB)] (2), [RhI(CO)(TXPB)] (3), [Rh(CO)(TXPB-F)] {(4); TXPB-F = {5-(2,7-di-tert-butyl-4-diphenylphosphino-9,9-dimethylthioxanthenyl)}diphenylfluoroborate]}, [Rh(CO)(TXPB)][PF6] (5) and [Rh(μ-H)(CO)(TXPB)] (6), respectively; the rhodium–borane and rhodium–co-ligand–borane coordination modes within these complexes are dependant on the co-ligand bound to rhodium (co-ligand = Cl, Br, I, F, H, or none in the case of cationic 5). Additionally, previously reported [(TXPB)Rh(μ-CO)2Fe(CO)Cp] (7) reacted with various isonitriles (CNR; R = C6H4Cl-p, 2,6-Me2-C6H3, nBu) to yield the bridging borataaminocarbyne complexes [(TXPB)Rh(μ-CO)(μ-CNR)Fe(CO)Cp] (8–10). The borane-free analogue of (7), [(TXPH)Rh(μ-CO)2Fe(CO)Cp] (11; TXPH = 2,7-di-tert-butyl-4-diphenylphosphino-9,9-dimethylthioxanthene), was synthesized for comparison, and reacted with CNC6H4Cl-p to yield [(TXPH)Rh(CO)(μ-CNC6H4Cl-p)2Fe(CO)Cp] (12), featuring two bridging isonitrile ligands. The TXPB ligand reacted with [PtMe2(cod)] (cod = 1,5-cyclooctadiene), forming [PtMePh(TXPB')] (13; TXPB' = 2,7-di-tert-butyl-5-methylphenylboryl-4-diphenylphosphino-9,9-dimethylthioxanthene), which exists in equilibrium with zwitterionic [PtMe(TXPB-Me)] (13') in solution. When heated, [PtMePh(TXPB')] (13) was converted to [PtPh2(TXPB'')] (14; TXPB'' = 2,7-di-tert-butyl-5-dimethylboryl-4-diphenylphosphino-9,9-dimethylthioxanthene) as an 86:14 equilibrium mixture with 13. Moreover, [PtMePh(TXPB')] (13) reacted with PPh3 and P(OPh)3 to provide neutral [PtMePh(PR3)(TXPB')] [R = Ph (15), OPh (16)], or with CNXyl to yield zwitterionic [PtMe(CNXyl)2(TXPB-Me)] (17; TXPB-Me = {5-(2,7-di-tert-butyl-4-diphenylphosphino-9,9-dimethylthioxanthenyl)}methyldiphenylborate). To address several limitations with the TXPB ligand, a new borane-containing ambiphilic ligand, FcPPB (26), was prepared in a seven step convergent synthesis from commercially available ferrocene and 1,2-dibromobenzene. The FcPPB ligand reacted with the Group 10 metal pre-cursors [Ni(cod)2], [Pd2(dba)3] (dba = trans,trans-dibenzylideneacetone) and [Pt(nb)3] (nb = norbornene), yielding co-ligand free [M(FcPPB)] complexes [M = Ni (28), Pd (29), Pt (30)] exhibiting κ2PP- and η3BCC-coordination of the FcPPB ligand. Alternatively, a trisphosphine-analogue of FcPPB, FcPPP (FcPPP = [Fe(η5-C5H4PPh2){η5-C5H4PtBu(C6H4PPh2-o)}]) (25), reacted with [Ni(cod)2] and [Pd2(dba)3] to form [{Ni(FcPPP)}2(μ-N2)] (33) and [Pd(η2-dba)(FcPPP)] (34), respectively. Platinum complex 30 reacted with CO, CNXyl and H2, providing [Pt(CO)(FcPPB)] (35), [Pt(CNXyl)(FcPPB)] (36) and [PtH(μ-H)(FcPPB)] (37), in which the borane is no longer η3BCC-coordinated; the arylborane in FcPPB is now engaged in η2BC-, η1B- and bridging Pt–H–B coordination, respectively. Moreover, [Pt(FcPPB)] (30) reacted with PhC2H to provide [Pt(C2Ph)(μ-H)(FcPPB)] (38), which rapidly isomerized to the vinylborane complex, [Pt(FcPPB')] (39; FcPPB' = [Fe(η5-C5H4PPh2)(η5-C5H4PtBu{C6H4BPh(CPh=CHPh-Z)-o})]). The FcPPB ligand also reacted with [Au(PPh3)][GaCl4] to yield [{Au(FcPPB)}2][GaCl4] (40) as a diastereomeric mixture, or with [W(CO)6] and [Ru3(CO)12] under photochemical and thermal conditions, respectively, to yield [W(CO)4(FcPPB*)] (41; FcPPB* = [Fe(η5-C5H4PPh2){η5-C5H3P(tBu)C6H4BPh-o}]) and [Ru3(μ-H)(CO)10(FcPPB**)] (42; FcPPB** = [Fe(η5-C5H4PPh2){η5-C5H3P(tBu)C6H4BPh2-o}]–), respectively. Both [W(CO)4(FcPPB*)] (41) and [Ru3(μ-H)(CO)10(FcPPB**)] (42) are products of intramolecular attack of the borane on the adjacent cyclopentadienyl-ring. Free FcPPB did not undergo any reaction under similar conditions. However, FcPPB reacted with B(C6F5)3 and BF3·OEt2 to yield FcPPB{B(C6F5)3} (43; [Fe(η5-C5H4PPh2{B(C6F5)3}){η5-C5H4PtBu(C6H4BPh2-o)}]) and [FcPPB-Ph][BF4] (44; [Fe(η5-C5H4PPh2){η5-C5H4PtBu(C6H4BPh-o)}]+), respectively; the former is a phosphine–borane adduct, whereas the latter is a bisphosphine-stabilized boronium cation. The coordination chemistry of a dimethylalane-appended analogue of FcPPB, FcPPAl (27), was also investigated; reaction with [Pt(nb)3] provided [Pt(η2-nb)(FcPPAl)] (45), which readily reacted with C2H4, C2Ph2, H2, and CO to provide [Pt(η2-C2H4)(FcPPAl)] (47), [Pt(η2-C2Ph2)(FcPPAl)] (48), [PtH2(FcPPAl)] (49) and [Pt(CO)(FcPPAl)] (50), respectively. Alternatively, heating a benzene solution of [Pt(η2-nb)(FcPPAl)] (45) yielded co-ligand free [{Pt(FcPPAl)}2] (46). All of the isolated platinum-FcPPAl complexes feature κ3PPAl-coordination of the FcPPAl ligand to platinum, and are the first unambiguous examples of η1Al-coordinated alkylalane complexes.
Keywords: Inorganic Chemistry; Ambiphilic Ligands